British Oncology Pharmacy Association Delphi consensus guidelines: Co-infusion of trometamol-containing calcium folinate (Leucovorin) with systemic anti-cancer treatments - TEZCAN, SONGÜL (My University, 2024)
Drug stability and compatibility are critical factors influencing the cost and logistics of treatment delivery, therapeutic effectiveness, and patient safety. This is particularly significant in the realm of cancer chemotherapeutics, where stability and compatibility studies play a vital role in ensuring rational and safe medicine administration. Oxaliplatin, fluorouracil, and irinotecan, commonly used in various combinations for gastrointestinal cancers, are complemented by co-administration of folinic acid in certain protocols. Notably, some folinic acid preparations include trometamol as an excipient, potentially impacting the stability of the chemotherapeutic agents if infused concomitantly. This study seeks to establish guidelines for oncology multidisciplinary teams, addressing potential risks associated with the combination of trometamol-containing folinic acid and chemotherapeutics. To achieve this, a quantitative questionnaire was distributed to members of the British Oncology Pharmacy Association (BOPA) and non-BOPA members through an online survey. Nineteen healthcare professionals with oncology experience, comprising 18 pharmacists and one nurse, completed the questionnaires. Each participant rated the validity and clarity of statements on a 5-point scale. The Delphi process concluded after the fourth round, consolidating the findings and recommendations from the multidisciplinary team. Twelve recommendations for safe practice have been made.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; ONKOLOJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; ONCOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji (tıbbi); Pharmacology (medical); Calcium folinate; compatibility; drug administration; folinic acid; irinotecan; Leucovorin; oxaliplatin; trometamol